EFEKTIFITAS MEDIA PEMBELAJARAN KAHOOT! TERHADAP MOTIVASI BELAJAR SISWA KELAS V PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR: KAJIAN LITERATUR - Muhsin; Hijjatul Helna; Majdina Rakha El Eisy; Nur Haliza; Ahmad Suriansyah; Wahdah Refia Rafianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research discusses the effectiveness of using Kahoot! as a learning medium to improve the learning motivation of fifth-grade students in the IPAS subject. The study was conducted through a literature review approach by examining various relevant recent studies. The synthesis results show that Kahoot! is able to create a more engaging learning atmosphere through elements of games, challenges, and immediate feedback. Data gathered from the analyzed studies indicate a significant increase in learning motivation after the implementation of Kahoot!, although its level of effectiveness falls into the moderate category. The improvement is particularly evident in students’ enthusiasm, active participation, and their drive to understand the material more deeply. Nevertheless, the effectiveness of Kahoot! is still influenced by several factors, such as device readiness, network quality, quiz design, and the teacher’s role in facilitating the activity. These findings reinforce that Kahoot! can serve as a relevant and adaptive learning medium that supports the goals of the Merdeka Curriculum, especially in strengthening the learning motivation of elementary school students.